Development and validation of a quantitative ultra performance LC® hydrophilic interaction liquid chromatography MS/MS method to measure fructose and sorbitol in human plasma. (19th March 2019) - Li, Fumin; Cousineau, Christopher; Xing, Gang; Raha, Nancy; Clemens, Sara; Mofikoya, Melissa; Kim, Moo-Young; Zhang, Jenny Yanhua
Aim: Fructose and sorbitol are utilized as biomarkers for nonalcoholic steatohepatitis. Measurement of fructose and sorbitol levels helps understanding disease progression, drug response and underlying mechanism.Materials & methods: Stable isotope-labeled fructose and sorbitol were used as surrogate standards and internal standards. Human plasma samples were processed and analyzed by ultra performance LC ® –MS/MS via chromatographic separation on a hydrophilic interaction liquid chromatography analytical column without derivatization. Assay was validated with biomarker fit-for-purpose concept.Results: A 12-min ultra performance LC ® –MS/MS method was developed and validated to directly measure fructose and sorbitol in human plasma with acceptable intra- and inter-assay precision and accuracy.Conclusion: This sensitive, selective, and high-throughput assay with suitable dynamic ranges was successfully applied to clinical studies to provide reliable fructose and sorbitol biomarker data.